Virtual world, defined from a technological perspective and applied to video games, mixed reality, and the Metaverse - Nevelsteen, Kim J. L. (Computer animation and virtual worlds, 2018)
There is no generally accepted definition for a virtual world, with many complimentary terms and acronyms having emerged implying a virtual world. Advances in networking techniques such as host migration of instances, mobile ad hoc networking, and distributed computing, bring in to question whether architectures can actually support a virtual world. Without a concrete definition, controversy ensues and it is problematic to design an architecture for a virtual world. Several researchers provided a definition but aspects of each definition are still problematic and simply can not be applied to contemporary technologies. The approach of this article is to sample technologies using grounded theory and to obtain a definition for a “virtual world” that is directly applicable to technology. The obtained definition is compared with related work and used to classify advanced technologies such as a pseudo‐persistent video game, a MANet, virtual and mixed reality, and the Metaverse. The results of this article include a break down of which properties set apart the various technologies; a definition that is validated by comparing it with other definitions; an ontology showing the relation of the different complimentary terms and acronyms; and the usage of pseudo‐persistence to categories those technologies, which only mimic persistence. This article provides a definition for virtual world, taking into account networking techniques such as, host migration of instances, mobile ad‐hoc networking, and distributed computing. An ontology is provided for complimentary terms and acronyms, and pseudo‐persistence is used to categories those technologies which only mimic persistence. Grounded Theory is used, with the novelty being that if new technology challenges the current theory, properties can be added to the theory and the definition updated.